Voltage instability identification with modified L-index using synchrophasor data - V. Vijaya Rama Raju; K. H. Phani Shree; S. V. Jayarama Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In the prevailing open-access environment, one of the limitations for power exchanges has been voltage stability. The study of voltage stability necessitates a complete network representation. In this paper, the advantage of the dynamic behavior of generators is considered by incorporating dynamic models for generators. It has been shown dynamic models resulted in more accurate results compared to the conventional PV buses or ideal voltage source models that are used in most of the voltage stability studies. Moreover, the traditional L-index is augmented by incorporating real-time and synchronized phasor data collected from the optimally located phasor measurement units (PMU) in a wide-area measurement system (WAMS) to estimate more accurate voltage stability margins. Simulation studies carried out on IEEE 9-bus and IEEE 14-bus systems under various system conditions. It has been demonstrated that the inclusion of dynamic models and synchrophasor data from WAMS significantly improves the precision with which voltage stability analysis results are obtained.